Is immunotherapy safe and effective in patients with VEXAS syndrome? - Chiara Marvisi; Francesco Muratore; Carlo Salvarani; Davide Nicoli; Enrico Farnetti; Lucia Spaggiari; Vincenza Ylenia Cusenza; Orsola Bonanno; Maria Banzi; Caterina Longo (Journal for ImmunoTherapy of Cancer)
The use of immune checkpoint inhibitors in VEXAS (vacuoles, E1 enzyme, X-linked, autoinflammatory, somatic) syndrome is unknown. Concerns are particularly about their safety, due to their potential capacity to exacerbate inflammatory symptoms. Further, there is a lack of data about their role in controlling the UBA1 clones. In this clinical case, we report a successful use of cemiplimab in a patient with VEXAS syndrome and a concomitant diagnosis of metastatic squamous cell carcinoma.